Prolegomena to a Cosmopolitanism in Deep Time. Issue 2 (3rd March 2016) - Robbins, Bruce
Abstract : When Assia Djebar ([1985] 1993) recounted the nineteenth-century French conquest of Algeria, was she obliged to recognize the earlier conquest of the Algerian Arabs by the Ottomans? Are we sure that this should not also count as colonialism? Was Djebar obliged, going even further back, to recognize the conquest by the Arabs of the Berbers? Would not this too have to be called an imperial conquest? The moment seems to have come when such awkward discipline-stretching issues are unavoidable. The cosmopolitanism with which we are familiar is geographical – an impulse to undo centuries of Eurocentrism by factoring in cultures and viewpoints from outside Europe and its settler colonies. But geographical cosmopolitanism entails a temporal cosmopolitanism that is less familiar – an expansion back in time to take in cultural texts, events and moments, like the classical canons of China and India or premodern empires, that are not merely non-European but also untethered to Europe by the usual relation of unequal power. This essay explores some alternative but not mutually exclusive descriptions of this move into deep time. Is it a depoliticizing shift from the postcolonial to 'world literature'? A necessary recalibration of the moral balance between 'our' and 'their' imperialisms? A return of 'grand narrative' in the name of ecology, or a 'new' materialism, or evolutionary science? A rehabilitation of European identity and European modernity?